The Influence Of Learning Environment, Facilities And Parents’ Social Status On The Learning Outcomes Of Fifth-Grade Elementary School Students - Dyah Ayu; Mulyadi Mulyadi; Ira Irviana (ALENA : Journal of Elementary Education, 2026)
This study aims to analyze the influence of the learning environment, learning facilities, and parents' social status on the learning outcomes of fifth-grade students at SDI Tangalla, particularly in Indonesian language subjects. The research is driven by the low student achievement, with only about 60% reaching the Minimum Mastery Criteria (KKM). A quantitative approach was employed using surveys and regression analysis. Data were collected through questionnaires, documentation, and observation of a sample of 60 students. The results indicate that all three independent variables—learning environment, learning facilities, and parents’ social status—have a significant simultaneous and partial influence on students’ academic performance. A supportive learning environment, adequate educational facilities, and higher socio-economic status of parents are positively correlated with improved learning outcomes. This study provides valuable insights for developing educational strategies that consider environmental, infrastructural, and socio-economic factors of students.